Refleksi Kritis Rekriminalisasi Penghinaan Presiden di Indonesia - Melissa B. Darbang (Syntax Corporation, 2023)
This study aims to examine the recriminalization of presidential insults by reviewing the democratic system applied in Indonesia. Since the passage of Bill Number 1 of 2023 concerning the Criminal Code (Law 1/2023), regulations related to insulting the president have become polemics in the community. The public considers that the arrangement of presidential insults is a manifestation of the government's efforts to silence the aspirations and voices of the people in democracy. The research method used is normative law research by conducting qualitative research on legal rules in laws and regulations. This research is descriptive in nature which aims to compile a systematic, factual and accurate description of the facts. This research will describe the state of law that applies in a certain place and a certain legal event that occurs in society. This research uses secondary data consisting of laws and regulations, books, journal articles or scientific magazines, papers, and scholarly opinion literature (doctrine). The results of this study show that the democratic system in Indonesia is also subject to Pancasila as Indonesia's philosophical foundation, so that the element of freedom in democracy cannot be misused as an attempt to humiliate. In addition, the regulation of the criminal act of insulting the president can be in line with the theory of legal objectives presented by Gustav Radbruch, namely fulfilling the elements of justice, certainty, and legal expediency, if applied wisely.